Prospects for the use of fecal microbiota transplantation in obese patients with Type 2 Diabetes Mellitus for weight loss and improvement of insulin sensitivity - E. V. Pokrovskaya (Endocrinology Research Centre, 2021)
Concerning the uncontrolled growth in the incidence of obesity and Type 2 Diabetes Mellitus (T2DM), numerous research have been carried out to study the pathogenetic mechanisms of progress of these diseases and development of new methods for their prevention and treatment in recent years. T2DM is known to be a multifactorial disease, in the development of which both lifestyle and various environmental factors, and genetic predisposition are involved. At the same time, in recent years, a theory has been discussed that intestinal dysbiosis, which is caused with quantitative and qualitative changes in the gut microbiota (GM) is one of the mechanisms of obesity and T2DM development. At the moment, various methods have been proposed for restoring the normal composition of GM, including the administration of prebiotics and metabiotics that stimulate the growth of gut flora, as well as probiotics, which directly include the necessary beneficial bacteria (mainly Bifidobacterium and Lactobacillus). Fecal microflora transplantation (FMT), which allows transferring an entire microbial community into the recipient's body, rather than individual bacteria is the newest and least studied method of GM normalization. In this connection, this method of GM influencing is of great interest for the prevention and treatment of metabolic diseases.